The Effect of Combined Foot Massage and Nature Music on the Sleep Quality of Critically Ill Patients - Nurhayati, Nunung; Waluyo, Agung; Kariasa, I Made; Asih, Sali Rahadi (STIKep PPNI Jawa Barat, 2024)
Aims: Critical patients in ICU and HCU often experience poor sleep due to excessive stress and various symptoms like environmental factors, pain, noise, anxiety, and physical discomfort. Foot massage and natural music interventions can help meet their sleep needs, providing a relaxing effect and improving physical and psychological conditions. The purpose of this study is to determine the effect of providing combination therapy of foot massage and natural music therapy in Dr. Hospital's peacock room Salamun 2023. Methods: This type of research is pre-experimental with a pre-post test of one group and uses the Richard Champbell Sleep Questionnaire (RCSQ). Then the data was processed using a paired sample T-test. The sample in this study is 16 respondents. Results: The results of the statistical test obtained a p-value of 0.01, meaning that there was an effect between the pretest and posttest of the combination of foot massage and natural music therapy on the quality of sleep in critical patients in the peacock room at Dr. Salamun Hospital, Bandung City, 2023. Conclusions : the conclusion of this study is that there is an effect of foot massage therapy and natural music on the sleep quality of critical patients as shown by the results of measuring the quality of critical patients before and after consecutive interventions with massage of both feet combined with natural music. For 10 minutes it has been proven to be able to improve sleep quality in critically ill patients so that this intervention can be applied as a therapy to improve sleep quality.